Hormonal input in plant meristems: A balancing act. - Galinha, C; Bilsborough, G; Tsiantis, M (2009)
Plant hormones are a group of chemically diverse molecules that control virtually all aspects of plant development. Classical plant hormones were identified many decades ago in physiology studies that addressed plant growth regulation. In recent years, biochemical and genetic approaches led to the identification of many molecular components that mediate hormone activity, such as hormone receptors and hormone-regulated genes. This has greatly contributed to the understanding of the mechanisms underlying hormone activity and highlighted the intricate crosstalk and integration of hormone signalling and developmental pathways. Here we review and discuss recent findings on how hormones regulate the activity of shoot and root apical meristems.